2022
DOI: 10.3390/plants11091198
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Comparative Transcriptome and Positively Selected Genes Reveal Adaptive Evolution in Leaf-Less and Root-Less Whisk Ferns

Abstract: While roots and leaves have evolved independently in lycophytes, ferns and seed plants, there is still confusion regarding the morphological evolution of ferns, especially in whisk ferns, which lack true leaves and roots and instead only exhibit leaf-like appendages and absorptive rhizoids. In this study, analyses of comparative transcriptomics on positively selected genes were performed to provide insights into the adaptive evolution of whisk fern morphologies. Significantly clustered gene families specific t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 49 publications
0
7
0
Order By: Relevance
“…Phylogenetic analyses revealed that homologs of both TF groups cluster with their counterparts from ophioglossoid ferns. This topology suggests that the evolution of the KNOX and WOX families took place before the separation of whisk ferns and ophioglossoid ferns (Xia et al, 2022).…”
Section: Monoplex Sams Producing Whisk Fern Leavesmentioning
confidence: 87%
See 4 more Smart Citations
“…Phylogenetic analyses revealed that homologs of both TF groups cluster with their counterparts from ophioglossoid ferns. This topology suggests that the evolution of the KNOX and WOX families took place before the separation of whisk ferns and ophioglossoid ferns (Xia et al, 2022).…”
Section: Monoplex Sams Producing Whisk Fern Leavesmentioning
confidence: 87%
“…Homologs of C1KNOX TFs are found in Psilotum nudum (Huang et al, 2020). WOX TF homologs from the T1 clade are found in P. nudum and Tmesipteris tannensis, and members of the T3 ("modern") clade are present in P. nudum (Xia et al, 2022). The presumable T2 clade homolog reported for P. nudum (Nardmann and Werr, 2012) Organogenesis in the monoplex SAM of whisk ferns.…”
Section: Monoplex Sams Producing Whisk Fern Leavesmentioning
confidence: 99%
See 3 more Smart Citations